Visually representing geo-temporal differences - Hoeber, O; Wilson, G; Harding, S; Enguehard, R; Devillers, R (2010 IEEE Symposium on Visual Analytics Science and Technology, 2010)
Data sets that contain geospatial and temporal elements can be challenging to analyze. In particular, it can be difficult to determine how the data have changed over spatial and temporal ranges. In this poster, we present a visual approach for representing the pair-wise differences between geographically and temporally binned data. In addition to providing a novel method for visualizing such geo-temporal differences, GTdiff provides a high degree of interactivity that supports the exploration and analysis of the data.